Case report: Mycobacterium chimaera-induced lymph node infection in a patient with chronic myeloproliferative neoplasm misdiagnosed as tuberculous lymphadenitis - Sun, Yingqian; Zhang, Chengliang; Lu, Bin; Chen, Jun; Pan, Xinling (Frontiers in Public Health, 2024)
Herein, we report a case of lymphadenitis caused by Mycobacterium chimaera. A 54-year-old woman with chronic myeloproliferative neoplasm was admitted to the hospital with cervical lymphadenopathy. After preliminary exclusion of various diseases such as lymphoma, Epstein–Barr virus infection, and autoimmune disease, a lymph node biopsy specimen showed epithelioid granulomatous lymphadenitis with caseous necrosis, epithelial-like cells, and multinucleated giant cells as seen in tuberculosis (TB). Although Mycobacterium tuberculosis was never isolated, diagnostic anti-TB treatment was commenced. Following over 9 months of treatment, there was no significant reduction in the size of her cervical lymph nodes, and she continued to experience recurrent low-grade fevers. One sample from the fourth lymph node biopsy tested negative for metagenomic next-generation sequencing (mNGS), and another sample tested positive in the BACTEC MGIT960 liquid culture system, identifying the strains as Mycobacterium chimaera. Anti-non-tuberculous mycobacteria (NTM) therapy was initiated, and the patient achieved symptom improvement. In conclusion, NTM lymphoid infection is easily misdiagnosed as long-term etiologic negativity.